PRODUCTION AND INCOME ANALYSIS OF PEANUTS FARMING IN SOUTH TOTIKUM SUBDISTRICT OF BANGGAI KEPULAUAN - Herman Mar'un; Made Antara; Lien Damayanti (AGROLAND: The Agricultural Sciences Journal, 2016)
This study aims to: (1) Determine the influence of land area, number of seeds, the amount of fertilizer and the amount of labor to the production of Non Hybrids peanuts variety in the District of South Totikum, and (2) Determine how much the Non hybrids peanut varieties farm income in the District of South Totikum. The sampling technique in this study is a simple random sampling method. Total population of around 200 non-hybrid peanut farmers. The amount of sample determine as much as 20% of the total population, so the number of samples used in this study were 40 respondents. Analysis of the data used Cobb-Douglass multiple linear regression analysis and the non-hybrid peanut farmer average income analysis. The results showed that the independent variable (Xi)jointly significant effect on the dependent variable (Y) non-hybrid peanut production, the value  of F count 70.903> F-table 4.46, Coefficient of determination R2 = 0.995 and R2 adjstsq = 0.995. means 99.5% Variation Value of non-hybrid peanut production (Y) can be explained by the variable land area (X1), the number of seeds (X2), fertilizers (X3), Labor (X4) and pesticides (X5) whereas 0.5 % more can be explained other models. Land area variable, number of seeds, fertilizer, labor, and pesticides, simultaneously can affect the production of non-hybrid peanut farm in the district of South Totikum. Coefficient regression/elasticity of the land area (X1)= 0.851, number of seeds (X2)= 0.066, the amount of fertilizer (X3)= 0,0,059, the amount of labor (x4)= -0.242 and pesticides (X5)= 0,049 on the level of α 0.01. The average production of non-hybrid peanuts cultivation of 1923.07 kg of dry pods/ha. The average income of non-hybrid peanuts farming are USD 10,254,962.12/ha per growing season.